Second-trimester maternal serum alpha-fetoprotein elevation and its association with adverse maternal/fetal outcome: ten years experience - Anfuso, S.; Soncini, E.; Bonelli, et al., P. (Acta Biomedica Atenei Parmensis, 2007)
Background: Alpha-fetoprotein (AFP) is the major serum protein in the embryonic stage and in the early fetal stage. The aim of this study was to determine any possible association between an “unexplained” elevation of maternal serum alpha-fetoprotein (MSAFP) levels in the second trimester of pregnancy and adverse maternal/fetal outcome. Methods: A retrospective cohort study, was carried out in the University of Parma, by reviewing all triple tests that had been found positive for neural tube defect screening, showing an “unexplained” MSAFP elevation (32.5 multiples of the median [MoM]), which could not be ascribed to any apparent reason. These results were compared with those of negative controls (MSAFP